The Influence of X – ray Polarization Degree on the Differential Scattering Cross - Section (Latakia University Journal -Basic Sciences Series, 2019)
This work aims to find the differential scattering cross-section  for  X-ray scattered by aluminum target with angles in intervals  in accordance to both polarization cases ( completely – partly).We found that the minimum and maximum values of  lies in the range .In addition, the relative scattered intensity and polarization degree have been presented as a function of scattered angles and the extreme values are found for each curve.